(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The present investigation assessed the soil organic carbon (SOC) stocks of four AEZs in Bangladesh which included AEZ 1 (Old Himalayan Piedmont Plain), AEZ 3 (Tista Meander Floodplain), AEZ 4 (Karatoya-Bangali Floodplain), and AEZ 9 (Old Brahmaputra Floodplain). Three land types high land (HL), medium high and (MHL) and low and (LL) were considered in the SOC assessment. The SOC stock was estimated by multiplying SOC (%) with bulk density (g/cc) and soil depth (cm). Across the AEZs and land types, the SOC (%) decreased with the increase in soil depth. The SOC (%) was the highest in the low land and the lowest in the high land over the AEZs. The soil bulk density in every AEZ increased with soil depth. Bulk density of soil for medium high and varied from 1.26 g/cc to 1.67 g/cc, for high and from 1.33 g/cc to 1.55 g/cc, and for low land it was 1.13 g/cc to 1.44 g/cc. The SOC stock at 0-20 cm depth was higher (14.19-4.67 t/ha) in low land followed by medium high land (8.25-4.58 t/ha) and high land (6.46-3.39 t/ha) for all AEZs. Among the four AEZs, the highest SOC stock was found in AEZ 1 irrespective of land types. DOI: http://dx.doi.org/10.3329/bjar.v38i4.18947 Bangladesh J. Agril. Res. 38(4): 625-635, December 2013